AB0206 Pan-Ppar Agonist IVA337 is Effective in Prevention and Treatment of Experimental Skin Fibrosis. (9th June 2015) - Ruzehaji, N.; Frantz, C.; Ponsoye, M.; Avouac, J.; Konstantinova, I.; Fromond, C.; Broqua, P.; Junien, J.L.; Allanore, Y.
Abstract : Background: Nuclear receptors are modulators of fibroblast activation which leads to tissue fibrosis, the hallmark of systemic sclerosis (SSc). Anti-fibrotic properties of rosiglitazone, a PPAR-γ agonist, have been reported previously, however clinical data suggesting cardiovascular complications may preclude further development in SSc. Other isoforms of PPARs, namely α and δ were shown to play a role in inflammation and fibrosis. IVA337 is a newly designed pan-PPAR agonist that showed a good safety profile in diabetic patients. Objectives: To determine the effect of IVA337 in pre-clinical models of SSc focusing on fibrotic skin lesions. Methods: Anti-fibrotic effects of IVA337 were studied in a mouse model of bleomycin-induced dermal fibrosis through the treatment of mice with an oral gavage at low 30 mg/kg and high 100 mg/kg doses. Rosiglitazone was administered at 5 mg/kg. Mouse fibrotic lesions were assessed using histology, immunohistochemistry, immunofluorescence, biochemical and molecular analysis. Human primary skin fibroblasts isolated from lesional SSc skin were used to assess the fibrotic response in vitro . Results: Immunofluorescence analysis of human lesional skin showed that both PPAR-α and γ isoforms were reduced in SSc compared to normal controls. In the mouse model of dermal fibrosis administration of IVA337 at the low dose decreased collagen content and number of α-SMA + myofibroblasts by 45±6% and 53±4%, p<0.05, whereas high dose decreased collagen content and number of α-SMA + myofibroblasts by 43±7% and 51±7%, p<0.01 respectively when compared to bleomycin-treated controls. Overall, anti-fibrotic property of IVA337 was found to be as effective as rosiglitazone. Apart from having anti-fibrotic effects, IVA337 also modulated expression of several markers of inflammatory cells when compared to bleomycin-treated rosiglitazone and vehicle controls. We carried out wound healing studies and ruled out the existence of adverse effects of IVA337 on wound closure despite its anti-fibrotic properties. In vitro, treatment of primary SSc fibroblasts with IVA337 inhibited migratory effect induced by TGF-β1. TGF-β1 promoted a robust pro-fibrotic response with significantly elevated collagen and α-SMA mRNA and protein levels, whereas in vitro treatment with IVA337 abrogated the stimulatory effects of TGF-β. In vitro treatment of fibroblasts with IVA337 decreased the level of phosphorylated-SMAD2/3 and interfered with TGF-β signalling pathway. Conclusions: IVA337 was shown to have a preventive effect in a mouse model of bleomycin-induced skin fibrosis and exerted a potent dampening effect in a model of established skin fibrosis. IVA337 interfered with TGF-β activation pathways and decreased collagen synthesis in primary human fibroblasts. Therefore, the use of pan-PPAR agonists may induce a broader spectrum of therapeutic effects and offer superior safety margin when compared to active agents targeting PPARγ in isolation. Taken together our results suggest that IVA337 might be an effective therapeutic approach in the treatment of SSc related fibrosis. Disclosure of Interest: None declared